Pengaruh Terpenuhinya Hak dan Kewajiban Mahasiswa terhadap Terciptanya Civic Equality dalam Mata Kuliah Pendidikan Kewarganegaraan - Maulida Faza; Yusuf Yusuf; Suparmi Suparmi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article examines the impact of fulfilling students' rights and responsibilities on citizenship equality in Civic Education using a qualitative approach. The study emphasizes the importance of balancing rights, such as access to fair education, and responsibilities, such as academic discipline, to create an inclusive academic atmosphere. Civic Education plays a role in instilling principles of nationality, democracy, and human rights, supporting equality in citizenship, particularly for marginalized groups. Students who understand the value of equality through Civic Education are predicted to become critical and responsible citizens, contributing to social justice and democracy.